Strategic unknowns: the usefulness of ambiguity and ignorance in organisational life - McGoey, L (2009)
From the subprime crisis, to the war on terror; from the politics of climate change to the rise of ‘evidence’ based medicine, this workshop will examine whether it is ignorance, and not knowledge, that serves as the main bulwark of economic, political and financial strength. In the context of global crises, whether financial, military or pandemic, is the ‘unknown’ increasingly being exploited as a strategic tool for personal and organisational survival?